2012
DOI: 10.3109/13685538.2012.699562
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled trial of testosterone gel on body composition and health-related quality-of-life in men with hypogonadal to low-normal levels of serum testosterone and symptoms of androgen deficiency over 6 months with 12 months open-label follow-up

Abstract: Six months 1% T gel improved body composition and HRQoL in symptomatic men with low to low-normal T, with further improvements over the following 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 44 publications
4
58
0
4
Order By: Relevance
“…Эти во-просы были сочтены экспертами как не вызывающие DOI: 10.14341/OMET2016315-31 Ожирение и метаболизм. 2016;13(3): [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] О б з о р ы л и т е р а т у р ы каких-либо противоречий, хотя другим лицам, не яв-ляющимся экспертами в данном вопросе, они могут представляться как якобы противоречивые, основы-ваясь на освещении в средствах массовой информа-ции. Тот факт, что по каждому из этих выводов было достигнуто единодушное одобрение, не следует интер-претировать ни как предположение об универсальном согласии всех экспертов по рассмотренным вопросам, ни как допущение об отсутствии прочих областей, за-служивающих серьезного обсуждения.…”
Section: методыunclassified
See 2 more Smart Citations
“…Эти во-просы были сочтены экспертами как не вызывающие DOI: 10.14341/OMET2016315-31 Ожирение и метаболизм. 2016;13(3): [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] О б з о р ы л и т е р а т у р ы каких-либо противоречий, хотя другим лицам, не яв-ляющимся экспертами в данном вопросе, они могут представляться как якобы противоречивые, основы-ваясь на освещении в средствах массовой информа-ции. Тот факт, что по каждому из этих выводов было достигнуто единодушное одобрение, не следует интер-претировать ни как предположение об универсальном согласии всех экспертов по рассмотренным вопросам, ни как допущение об отсутствии прочих областей, за-служивающих серьезного обсуждения.…”
Section: методыunclassified
“…Возраст не является специфичным фактором риска развития дефицита тестостерона, в связи с чем тер-мин «возрастной гипогонадизм» искажает реальную DOI: 10.14341/OMET2016315-31 Ожирение и метаболизм. 2016;13(3): [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] О б з о р ы л и т е р а т у р ы картину. У большинства мужчин, даже в пожилом воз-расте, концентрации тестостерона остаются в пределах нормального диапазона.…”
Section: заявление 3 дт представляет угрозу общественному здоровью вunclassified
See 1 more Smart Citation
“…Erectile dysfunction has been identified as a composite pathology of metabolic risk factors, smoking and depression, whereas only TT concentrations below 8 nmol/L contributed to that symptom (p ¼ 0.003). Behre [66] demonstrated that 6 months of TRT improved body composition and HRQoL in men aged 50-80 years with TT515 nmol/L and LOH symptoms; these men showed further improvements in body composition and HRQoL over the following 12 months of TRT. Lower TT levels have also been shown to be associated with sub-threshold symptoms of anxiety and depression [67].…”
Section: Recommendation 3: Laboratory Diagnosismentioning
confidence: 99%
“…Despite having low specificity, the AMS and other male hypogonadism questionnaires may be useful for monitoring the clinical response to testosterone replacement therapy (TRT) [7][8][9][10]. The AMS and other questionnaire may be useful to monitor results of testosterone therapy as well as to assess the presence and severity of symptoms as a prerequisite for initiating TRT [11].…”
Section: Recommendation 2: Clinical Diagnosismentioning
confidence: 99%